Junie B. Jones and the Mushy Gushy Valentines - Park, Barbara (New York Random House, 1999)
When Junie B. Jones receives a mushy gushy "valentine" on Valentine's Day, she tries to find out who in her kindergarten class is her secret admirer.
Keywords: Valentine's Day - Fiction; Valentines - Fiction; Kindergarten - Fiction; Schools - Fiction